ChemInform Abstract: Flux‐Mediated Syntheses, Structural Characterization and Low‐Temperature Polymorphism of the P‐Type Semiconductor Cu2Ta4O11. Issue 24 (27th May 2016) - King, Nacole; Sullivan, Ian; Watkins‐Curry, Pilanda; Chan, Julia Y.; Maggard, Paul A.
Abstract: α‐Cu2 Ta4 O11 is prepared in a molten CuCl‐flux by the reaction of nanocrystalline Cu2 O and Ta2 O5 in the molar ratio of 2:1 (evacuated silica tubes, 665 °C, 1 h).